Effects of thermal treatment and weathering in the resistance against termites of a fast-growing pine wood - Ricardo Ripoll de Medeiros; Andrey Pereira Acosta; Kelvin Techera Barbosa; Rafael de Avila Delucis; Rafael Beltrame; Darci Alberto Gatto (Maderas: Ciencia y Tecnología, 2023)
This work deals with the resistance against subterranean termites of a thermally treated and weathered fast-growing pine wood. The pine wood was thermally treated at variable temperatures (c.a. 180 ºC, 200 ºC, and 220°C) for 2 h and then exposed to artificial weathering for three months. Chemical, hygroscopic, thermal, mechanical, colorimetric, biological, and morphological characteristics were evaluated. Compared to the untreated wood, as expected, the thermal treatments yielded wood parts with improved thermal, hygroscopic and colorimetric features. The thermal treatment also helped for retaining the thermal stability, volumetric hydrophobicity, color, and roughness of the pine wood exposed to the weathering. Previous changes ascribed to the weathering process did not affect the damages attributed to the termites attack, although that wood treated at 180 ºC presented an increased resistance against the termites deterioration.